Enhancing jump performance after combined vs. maximal power, heavy resistance, and plyometric training alone - de Villarreal, E. S. S.; Izquierdo, M.; Gonzalez-Badillo, J. J. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to examine the effects of 5 different stimuli on jumping ability and power production after 7 weeks of training. Sixty-five (47 men and 18 women) physical education students were randomly assigned to 5 experimental groups that performed: combination of all training methods (A); heavy-resistance training using full-squat exercise (i.e., 56-85% of 1 RM for 3-6 repetitions) (B); power-oriented strength training using a parallel-squat exercise (i.e., 100-130% of load that maximizes power output for 2-6 repetitions) (C); power-oriented strength training using a loaded countermovement jumping (i.e., 70-100% of load that maximizes power output for 2-5 repetitions; countermovement jump [CMJ]) (D); and plyometric jumping (E). The CMJ (cm), loaded CMJ (cm), maximum rate of force development (RFDmax) during early concentric phase of loaded CMJ (N/s) and power output during early concentric phase of loaded CMJ (watts) were measured before and after 7 weeks of training. Significant improvements in CMJ (from 7.8 to 13.2%) were observed in all groups. Significantly greater increases in power output during loaded jumps were observed in A (10-13%) and D (8-12%) groups compared with in the other groups. Significant increases in RFDmax were observed in A (20-30%), C (18-26%), and D (20-26%) groups. The results of this study provide evidence to suggest that if training program is designed and implemented correctly, both traditional slow velocity training and faster power-oriented strength training alone, or in combination with plyometric training, would provide a positive training stimulus to enhance jumping performance.